1993
DOI: 10.1177/095646249300400104
|View full text |Cite
|
Sign up to set email alerts
|

Genital Human Papillomavirus Infections: Correlation of Cytological, Colposcopic and Histological Features with Viral Types in Women and Their Male Partners

Abstract: To determine the incidence of anogenital papillomavirus infections and to assess the value of available diagnostic methods, we compared the cytological, colposcopic and histological features of anogenital papillomavirus-related lesions with their associated human papillomavirus types (HPV) in 300 women and in their male partners. HPV-type deoxyribonucleic acid was detected by blot hybridization in 398 out of 624 subclinical and clinically defined anogenital lesions. Whatever the site of the lesion, condylomas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 45 publications
3
10
0
1
Order By: Relevance
“…These data support the sexual transmission of HPVs, but the presence of HPV-6 DNA in one virginal woman raises the possibility of alternative routes of viral acquisition. Discrepancies in the HPV type(s) detected in monogamous partners (Ho et al, 1993) and discordance of HPV-16/18 between married couples has also been documented (Monsonego et al, 1993;Hippelainen et al, 1994). However, these findings describe current infection(s) and it is possible they include a dominant HPV type acquired before the present partner.…”
Section: Introductionmentioning
confidence: 82%
“…These data support the sexual transmission of HPVs, but the presence of HPV-6 DNA in one virginal woman raises the possibility of alternative routes of viral acquisition. Discrepancies in the HPV type(s) detected in monogamous partners (Ho et al, 1993) and discordance of HPV-16/18 between married couples has also been documented (Monsonego et al, 1993;Hippelainen et al, 1994). However, these findings describe current infection(s) and it is possible they include a dominant HPV type acquired before the present partner.…”
Section: Introductionmentioning
confidence: 82%
“…Whilst women with low-risk HPV infections had male partners with identical HPV types in 50 and 37% of cases, respectively, the rate of concordance was much lower amongst those with high-risk HPV-16 or HPV-18 infections (24 and 16%). Another study of heterosexual partners using dot-blot assays found a concordance between partners with HPV-16 infections of 57% and of just 29% for HPV-18 [8]. Unfortunately, interpretation of such studies is frequently confounded by the inclusion of short-term and non-monogamous relationships.…”
Section: Sexual Transmission Of High-risk Hpvsmentioning
confidence: 99%
“…Quoi qu'il en soit, la cytologie est bien entendu nécessaire et indispensable chez ces patientes. La colposcopie apportant des éléments d'information complémentaire en particulier pour l'évaluation des sites génitaux externes que le frottis ne permet pas de relever, sous réserve de ne pas passer dans l'excès de la surévaluation et du surdiagnostic [61].…”
Section: Partenaire Présentant Des Lésions à Hpvunclassified